The use of games in a graduation course in an engineering faculty - De Oliveira Rangel Salibi, José Geraldo [UNESP]; Machado, Bruna Andrade [UNESP]; De Souza Rodrigues, José [UNESP]; Souza, Fernando Bernardi [UNESP]; De Campos, Renato [UNESP] (My University, 2021)
The quality of education did not accompany the Brazilian effort to increase the number of students in higher education, contributing to this the small number of practical classes and interdisciplinarity. The publication in 2019 of the new National Curriculum Guidelines changed the focus of content-based teaching to teaching focused on skills development. Game-Based Learning (GBL) generates greater engagement, motivates action, promotes learning and problem solving in a creative way and reduces resistance in the face of complex themes. In the researched institution it was observed that since 1999 there are experiences with the development and use of games. Among the games found there are simulations and games in digital and board format. The main games used are the Beer Distribution Game and the Lean Board Game, in board format, and the games Bomburguer, Lemonade Stand Game, Virtual Market, Strategy and Sustainability Simulation, Strategy Simulation, Production Planning Simulation, Simulated Model in PROMODEL, Kanban Game and Distribution Game. The games found focus on teaching production management and logistics, strategy and sustainability. Some of the games used focus more on the technical aspects of a specific concept, such as the Lean Board Game, Kanban Game and Goldratt Simulator games. Production Engineering courses has many interfaces with other areas and there are possibilities to expand the use of games in that institution, contributing to the improvement of teaching and expanding the use of active methodologies in its courses. The research is a case study and was carried out in the following stages: the first sought to find the games used in a course, then the games used in the area and, finally, compared the curriculum with the games found in the area. It is concluded that there is space to expand the use of games and, consequently, the adoption of active methodologies in the analyzed course.
Keywords: Game-based learning; Production engineering course; Serious games